Microfluidics for Biosensing - Feng, Shilun; Asadnia, Mohsen; Li, Ming (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
There are 12 papers published with 8 research articles, 3 review articles and 1 perspective. The topics cover: Biomedical microfluidics Lab-on-a-chip Miniaturized systems for chemistry and life science (MicroTAS) Biosensor development and characteristics Imaging and other detection technologies Imaging and signal processing Point-of-care testing microdevices Food and water quality testing and control We hope this collection could promote the development of microfluidics and point-of-care testing (POCT) devices for biosensing.